Analysis of PIONEER Co-curricular Program and Learning Habit Development in SMK Negeri 3 Salatiga - Deviana, Risfa; Saputri, Aninda Esadilla; Kamalvi, Meisa; Winarno, Winarno (Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing demand for industry-ready graduates requires vocational schools to develop curricula that strengthen students’ character, work ethic, and learning habits. However, discrepancies remain between industrial expectations and school practices, especially regarding students’ discipline, parental support, and school facilities. This study aims to analyze the PIONEER co-curricular program at SMK Negeri 3 Salatiga and its role in developing students’ learning habits within an industry-based culture. Using a qualitative descriptive method, data were collected through interviews, observations, and document analysis involving the vice principal for curriculum and teachers. The findings reveal that PIONEER strengthens discipline, work ethics, collaboration, and students’ adherence to industrial values, despite challenges related to teacher perceptions, parental involvement, financial constraints, and limited facilities. The study concludes that PIONEER serves as a strategic initiative to align vocational education with real workplace demands while cultivating students’ readiness and character.Keywords: co-curricular program, industry-based curriculum, learning habits, vocational education, PIONEER program